Tobacco industry tactics for resisting public policy on health - (:unkn) unknown (WORLD HEALTH ORGANIZATION, 2000)
The tactics used by the tobacco industry to resist government regulation of its products include conducting public relations campaigns, buying scientific and other expertise to create controversy about established facts, funding political parties, hiring lobbyists to influence policy, using front groups and allied industries to oppose tobacco control measures, pre-empting strong legislation by pressing for the adoption of voluntary codes or weaker laws, and corrupting public officials. Formerly secret internal tobacco industry documents provide evidence of a 50-year conspiracy to resist smoking restrictions, restore smoker confidence and preserve product liability defence. The documents reveal industry-wide collusion on legal, political and socially important issues to the tobacco industry and clearly demonstrate that the industry is not disposed to act ethically or responsibly. Societal action is therefore required to ensure that the public health takes precedence over corporate profits. Recommendations for reducing the political influence of the tobacco industry include the following. Every tobacco company in every market should publicly disclose what it knew about the addictiveness and harm caused by tobacco, when it obtained this information, and what it did about it. The industry should be required to guarantee internationally recognized basic consumer rights to its customers. Trade associations and other industry groupings established to deceive the public should be disbanded. These recommendations should be incorporated into WHO's Framework Convention on Tobacco Control.
Keywords: tobacco industry, legislation; public policy; health policy; persuasive communication; mass media; propaganda; public relations; treaties